2001
DOI: 10.1080/17450390109381975
|View full text |Cite
|
Sign up to set email alerts
|

Further survey of the occurrence offusariumtoxins in wheat grown in southwest Germany

Abstract: A total of 53, 54, 57, 52 and 60 wheat samples for feed use were collected randomly after the 1989, 1990, 1991, 1992 and 1993 crops, respectively, from farms in an area of southwest Germany. Deoxynivalenol (DON), 3- and 15-acetyldeoxynivalenol (3-, 15-ADON), nivalenol (NIV), HT-2 toxin (HT-2), T-2 toxin (T-2), diacetoxyscirpenol (DAS), and fusarenon-X (FUS-X) were determined by gas chromatography, combined with mass selective detection (GC-MS), zearalenone (ZEA), alpha- and beta-zearalenol (alpha-beta-ZOL) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…DON content was in the range from 15 to 965 µg/kg in white flour and from 15 to 1379 µg/kg in wholegrain flour (Schollenberger et al 2002). These results are in good agreement with the earlier German study (Müller et al 1997(Müller et al , 2001, in which the number of DON positive cereals was in the range from 83% to 96%. An extensive survey focused on trichothecene mycotoxins in cereal grains was recently conducted in Croatia (Sokolovic & Šimpraga 2005).…”
supporting
confidence: 82%
“…DON content was in the range from 15 to 965 µg/kg in white flour and from 15 to 1379 µg/kg in wholegrain flour (Schollenberger et al 2002). These results are in good agreement with the earlier German study (Müller et al 1997(Müller et al , 2001, in which the number of DON positive cereals was in the range from 83% to 96%. An extensive survey focused on trichothecene mycotoxins in cereal grains was recently conducted in Croatia (Sokolovic & Šimpraga 2005).…”
supporting
confidence: 82%
“…The highest level of NIV was detected in one sample containing oats. It was clear from this work that contamination by DON and NIV is not only exclusive of corn but also of oat and wheat contents as some authors have reported for these ingredients (Mü ller et al, 1997(Mü ller et al, , 1998(Mü ller et al, , 2001Langseth and Rundberget, 1999;Schollenberger et al, 2002Schollenberger et al, , 2005a.…”
Section: Occurrence Of Don and Niv In Corn-based Foodsmentioning
confidence: 60%
“…Overall, although the mycotoxin levels found in this survey were low it is important, however, to bear in mind that cereals are only one of the many possible sources of these mycotoxins for humans, specially children or young people. Moreover, Fusarium contamination in grains may differ among the years of harvest (Langseth and Elen, 1997;Mü ller et al, 1997Mü ller et al, , 2001Scott, 1997). Thus, different levels of toxin contamination can also be expected for cereal-based foods.…”
Section: Article In Pressmentioning
confidence: 97%
“…It was also reported that contamination with NIV was more frequently reported in oriental countries (Tanaka, Sago, Zheng, Nakagawa, & Kushiro, 2007, 2010, whereas DON was the major toxin in Canada, USA and EC countries (Gottschalk, Barthel, Engelhardt, Bauer, & Mayer, 2009;Lattanzio, Solfrizzo, Powers, & Visconti, 2007;Schaafsma & Hooker, 2007). Moreover, Fusarium infestations and the mycotoxin contents are dependent on the cereal species grown and on changes in production methods, and levels can vary year-by-year because of climate change (Langseth & Elen, 1997;Müller, Reimann, Schumacher, & Schwadorf, 2001;Scott, 1997). Thus, different levels of 8-ketotrichothecenes contamination can also be expected for cereals and their processed products.…”
Section: Analyzed 11mentioning
confidence: 89%